Light Intensity Stimulates the Production of Extracellular Polymeric Substances (Eps) in a Culture of the Desert Cyanobacterium Trichormus Sp - Ortiz-Calderon, C; Dahech-Levenberg, P (Springer Science and Business Media B.V., 2021)
Cyanobacteria are photoautotrophic organisms that inhabit diverse environments. Some species have been characterized for their production of extracellular polymeric substances (EPS) that have several biotechnological applications. EPS production is dependent on the growth conditions of the cyanobacteria, such as the content of nitrogen in the culture medium, the supplementation of the media with NaCl, or the light intensity. In this work, we studied the production profile of EPS at different growth stages in a culture from desert of the cyanobacterium Trichormus sp. The culture had been obtained from biological soil crusts (BSC) collected from a semi-arid zone of the IV region of Chile. We evaluated the effect of NaCl and nitrogen content in the culture media, in addition to the light intensity, on the growth and EPS production of the cyanobacterial cultures. The growth curve of Trichormus sp. showed a lag phase up to day 6, a short exponential phase up to day 10, and a stationary phase that lasted to the end of the experiment. The production of EPS was evaluated during the exponential growth phase of Trichormus sp. and showed a fourfold EPS production at 9.6 W m−2, compared to the basal condition at 3.2 W m−2. This light intensity is the highest light condition reported for the evaluation of EPS production in soil cyanobacteria. In this work, we show that the light intensity, but not the presence of NaCl or nitrogen in the medium, stimulates the production of EPS in the desert cyanobacterium Trichormus sp. © 2021, The Author(s), under exclusive licence to Springer Nature B.V.